Graphene oxide prepared by graphene nanoplatelets and reduced by laser treatment. (10th May 2017) - Longo, A; Verucchi, R; Aversa, L; Tatti, R; Ambrosio, A; Orabona, E; Coscia, U; Carotenuto, G; Maddalena, P
Abstract: The Hummers' method for graphite oxide (GO) preparation has been applied to graphite nanoplatelets, in order to achieve higher reaction yield and faster kinetics. Aqueous GO solutions have been used to produce uniform GO films on a polyethylene terephthalate substrate, generating graphene patterns in a controlled way (widths of a few tens of microns). The reduction of GO deposited on the polymeric substrate has been performed by using a Nd:YVO4 continuous-wave frequency-duplicated laser. Spectroscopic and diffractometric characterizations (FT-IR, visible-NIR, Raman, XPS, and XRD) have shown that the reduction process induced by the laser annealing technique is mainly due to dehydration of the GO layers. It has been obtained by means of a suitable laser optical apparatus, a controlled reduction of GO without damaging the substrate, and precise writing of micro-tracks that can be used as electrically and thermally conductive patterns.